Identification and molecular characterization of Otobius megnini (Ixodida: Argasidae) seen in humans in Muş province, Turkey - Ayşe Karakuş; Ali Bilgin Yilmaz; Servet Karaca; Bilal Dik; Vural Denizhan (Persian Journal of Acarology)
Otobius megnini (Ixodida: Argasidae) is a cosmopolitan soft tick that parasitizes humans as well as domestic and wild animals. The larval and nymph stages of this tick usually feed by parasitizing in the ear canal. The material of this study consists of ticks collected during ear cleaning in approximately 496 people coming with the complaint of ear pain in state hospitals in Bulanik and Malazgirt districts of Muş province, eastern Turkey. As a result of microscopic examination performed on ticks collected from humans, O. megnini tick was determined and molecular identification was made for definitive diagnosis. The 16S rRNA gene fragment of the tick was amplified by PCR. Obtained PCR products were 360 bp. The PCR products were analyzed by sequence analysis and compared with the reference sequences in the BLAST and Genbank. A phylogenetic tree was created with MEGA 7 software using Maximum Likelihood model. As a result, the previously identified Otobius megnini in Turkey, was confirmed using molecular methods for the first time.